Habitat‐based biodiversity assessment for ecosystem accounting in the Murray–Darling Basin. Issue 5 (27th May 2022) - Mokany, Karel; Ware, Chris; Harwood, Thomas D.; Schmidt, Rebecca K.; Ferrier, Simon
Abstract: Understanding how biodiversity is changing over space and time is crucial for well‐informed decisions that help retain Earth's biological heritage over the long term. Tracking changes in biodiversity through ecosystem accounting provides this important information in a systematic way and readily enables linking to other relevant environmental and economic data to provide an integrated perspective. We derived biodiversity accounts for the Murray–Darling Basin, Australia's largest catchment. We assessed biodiversity change from 2010 to 2015 for all vascular plants, all waterbirds, and 10 focal species. We applied a scalable habitat‐based assessment approach that combined expected patterns in the distribution of biodiversity from spatial biodiversity models with a time series of spatially complete data on habitat condition derived from remote sensing. Changes in biodiversity from 2010 to 2015 varied across regions and biodiversity features. For the entire Murray–Darling Basin, the expected persistence of vascular plants increased slightly from 2010 to 2015 (from 86.8% to 87.1%), mean species richness of waterbirds decreased slightly (from 12.5 to 12.3 species), whereas for the focal species the estimated area of habitat increased for 8 species and decreased for 1 species. Regions in the north of the Murray–Darling Basin generally had decreases in biodiversity from 2010 to 2015, whereas in the south biodiversity was stable or increased. Our results demonstrate the benefits of habitat‐based biodiversity assessments in providing fully scalable biodiversity accounts across different biodiversity features, consistent with the United Nations System of Environmental Economic Accounting – Ecosystem Accounting (SEEA EA) framework. Abstract : Evaluación de la Biodiversidad con base en el Hábitat para la Contabilización de Ecosistemas en la Cuenca Murray‐Darling Resumen: El conocimiento sobre cómo está cambiando la biodiversidad en el tiempo y en el espacio es crucial para las decisiones bien informadas que ayudan a retener la herencia biológica de la Tierra a largo plazo. El seguimiento de cambios en la biodiversidad mediante la contabilidad de los ecosistemas proporciona esta información importante de manera sistémica y permite fácilmente la conexión con otros datos ambientales y económicos relevantes para proporcionar una perspectiva integrada. Derivamos la contabilidad de la biodiversidad para la Cuenca Murray‐Darling, la mayor cuenca de Australia. Analizamos los cambios en la biodiversidad entre 2010 y 2015 de todas las plantas vasculares, todas las aves acuáticas y diez especies focales. Aplicamos una estrategia de evaluación basada en el hábitat que combinó los patrones esperados en la distribución de la biodiversidad a partir de modelos espaciales de la biodiversidad con una serie temporal de datos espacialmente completos derivados de la teledetección de la condición del hábitat. Los cambios en la biodiversidad entre 2010 y 2015 variaron entre las regiones y las características de la biodiversidad. Para toda la Cuenca Murray‐Darling, la persistencia esperada de las plantas vasculares incrementó ligeramente durante los años de estudio (de 86.8% a 87.1%), la riqueza promedio de especies de aves acuáticas disminuyó un poco (de 12.5 a 12.3 especies), mientras que el área estimada del hábitat de las especies focales incrementó para ocho especies y disminuyó para una. Las regiones al norte de la cuenca tuvieron disminuciones generalizadas de la biodiversidad entre 2010 y 2015, mientras al sur, la biodiversidad se mantuvo estable o incrementó. Nuestros resultados demuestran los beneficios que tienen las evaluaciones de la biodiversidad basadas en el hábitat para proporcionar una contabilidad de la biodiversidad completamente escalable entre las diferentes características de la biodiversidad, acorde con la estructura del Sistema de Contabilidad Económico‐Ambiental – Contabilidad de los Ecosistemas (SEEA EA) de las Naciones Unidas. 【摘要】: 了解生物多样性的时空变化对于制定帮助地球生物遗产长期续存的决策至关重要。通过生态系统核算追踪生物多样性的变化, 可以系统地提供这一重要信息, 并能随时与其他相关的环境和经济数据相联系, 提供综合性视角。本研究对澳大利亚最大的集水区——墨累达令盆地的生物多样性进行了核算, 评估了2010年到2015年所有维管植物、所有水鸟和10个重点保护物种的生物多样性变化。我们采用了一种尺度可变的基于栖息地的评估方法, 整合了空间生物多样性模型的生物多样性分布格局估计与遥感得到的栖息地状况空间完整数据的时间序列。研究发现, 2010年至2015年, 生物多样性的变化在不同地区和生物多样性特征之间有所差异。整个墨累达令流域维管植物的预期续存情况在2010年到2015年略有增加(从86.8%到87.1%), 水鸟的平均物种丰富度略有下降(从12.5种到12.3种), 而重点保护物种中8个物种的栖息地面积预计增加, 1个物种的栖息地面积下降。此外, 墨累达令盆地北部地区的生物多样性从2010年到2015年普遍下降, 而南部地区的生物多样性则保持稳定或有所增长。我们的结果表明, 基于栖息地的生物多样性评估有助于提供不同生物多样性特征全尺度的生物多样性核算, 这也符合联合国环境经济核算体系‐生态系统核算(SEEA EA)框架。【翻译:胡怡思;审校:聂永刚】